Leadership Behaviours and Organisational Commitment Mediated by Job Satisfaction of Academic Staff at Kyambogo University - Kato, Joshua Kimata; Mugizi, Wilson; Kasule, George Wilson; Kyozira, Peter (East African Journal of Education Studies, 2024)
This study examined the influence of leadership behaviours on the job satisfaction of the academic staff of Kyambogo University in Uganda. Specifically, the study examined the influence of participative, supportive, directive and achievement-oriented leadership on the job satisfaction of academic staff in Kyambogo University, Uganda. Job satisfaction was studied in terms of intrinsic and extrinsic job satisfaction. Using the quantitative approach for inferential analysis, the study adopted the correlational research design on a sample of 175 full-time academic staff. The study used a self-administered questionnaire to collect the data. Data analysis involved carrying out Structural Equation Modelling (SEM) using SmartPLS. The results indicated that while participative, supportive and directive leadership positively and significantly influenced the job satisfaction of full-time academic staff, achievement-oriented leadership had a negative and insignificant influence on the job satisfaction of academic staff. The study concluded that while participative, supportive and directive leadership behaviours are imperative for the job satisfaction of full-time academic staff, achievement-oriented leadership is not. Therefore, it was recommended that to boost the job satisfaction of academic staff, managers of universities should promote participative, supportive and directive leadership than achievement-oriented leadership